Thalassaemia detection using CBR Algorithm via mobile device - Nur Faezah, Omar (2011)
This thesis proposes a Case-Based Reasoning model for medical diagnosis,particularly for Thalassaemia diagnosis. CBR Algorithm is an algorithm that can solve a new problem by remembering a previous similar situation and by reusing information and knowledge of that situation in a new situation.CBR is suit for solving the problem in Thalassaemia cases.The model is designed and prototype is developed to test the diagnosis accuracy of the model.T his application is focus on Beta Thalassaemia and Haemoglobin E Trait only.For platform, this application will be using the mobile device such as PDA. Moreover,this application will be using the programming language Visual Basic. Net applied in Visual Studio 2008.The methodology has chosen is rapid application development (RAD) where this method is the archive with apparel search requirement. The results show that the Case-Based Reasoning model has a great potential to be implemented in diagnosing Thalassaemia cases.